Performance and Acceptability of the FC2 Female Condom When Used With and Without a Silicone Placebo Vaginal Ring—A Randomized, Crossover Trial. (1st September 2020) - Nel, Annalene; Malherbe, Mariëtte; van Niekerk, Neliëtte; Beksinska, Mags; Greener, Ross; Smit, Jennifer; Frezieres, Ron; Walsh, Terri
Abstract : Background: The silicone Dapivirine Vaginal Ring 25 mg, has been developed to provide an additional HIV prevention option for women. If approved for use, women will always be counselled to use condoms when using the vaginal ring for maximum protection. This paper evaluates the compatibility of female condoms with the ring. Methods: This was a 2-period crossover, randomized noninferiority trial. Couples in 2 sites in the United States of America were randomized to FC2 Female Condom (FC2) with and without a placebo silicone ring and asked to use 4 female condoms in each period. The primary noninferiority endpoint was the clinical failure rate during intercourse or withdrawal (self-reported clinical breakage, slippage, misdirection, and invagination). Frequencies and percentages were calculated for each failure mode and differences in performance of the 2 periods, using the female condom without the ring as reference. Noninferiority was defined using an 8% margin at the 5% significance level. Safety and tolerability were also assessed. Results: Eighty-one couples were enrolled and 79 completed the trial using a total of 596 female condoms (297 and 299 with/without a ring inserted, respectively). Total female condom clinical failure was 14.1% and 15.7% in the presence and absence of a ring, respectively, with a difference of −2.1% (95% confidence interval: −7.8% to 3.6%), thereby demonstrating noninferiority when used with the ring. There were no differences in safety and tolerability between the 2 periods. Discussion: Concurrent use of the placebo silicone vaginal ring had no significant effect on female condom functionality or safety outcomes.